Semiotic Representation of Local Wisdom in Southeast Asian Folk Narratives - Nissa Aurellia Putri; Elinda Novita Dewi; Wan Muna Marwah (Journal of Literary and Linguistic Research, 2026)
This empirical qualitative study investigates the semiotic representation of local wisdom in Southeast Asian folk narratives across Malay, Bugis, and Thai communities, integrating textual, performative, and ritualized data to examine how ethical, ecological, and social knowledge is encoded and transmitted. Using purposive sampling, the research collected oral narratives, manuscripts, visual artifacts, and direct observations of storytelling and ritual performances, complemented by semi-structured interviews with community elders and knowledge holders. Data analysis employed thematic and semiotic content analysis grounded in Saussurean, Peircean, and ecosemiotic frameworks, coding indexes, icons, and symbols across multimodal contexts. Results demonstrate that multimodal semiotics—including gestures, costume motifs, vocal modulation, and symbolic repetition—function as pedagogical and ethical devices that reinforce comprehension and memory among participants. Comparative analysis highlights both functional universality and cultural specificity, with symbolic motifs conveying ecological stewardship, moral responsibility, and social norms consistently across communities. The study further shows that digital and performative adaptations preserve semiotic density while expanding interpretive reach. The findings contribute to theoretical frameworks of semiotics, cultural pedagogy, and knowledge transmission, offering methodological guidance for future empirical research on folk narratives.